Timeliness of annual audit report: some empirical evidence from Malaysia - Shukeri, Siti Norwahida; Puat Nelson, Sherliza (2011)
The aim of this study is to examine the factors that influence annual audit report in Malaysia. The sample includes 300 largest companies listed in the KLSE for the year ended 2009. Findings show that audit report lag is significantly influenced by auditor type, audit opinion and firm performance. However, no evidence was found to support the effect of board independence, audit committee size, audit committee meetings and audit committee qualifications on audit report lag. Apart from contributing to the literature on determinants of audit timeliness, this study also falls under the strand of literature that examines the consequences of the regulatory changes introduced around the world to strengthen corporate governance and financial reporting transparency, hence provide evidences of recent audit delays.